(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This thesis examines the characteristics of Modernism in English literature through the works of James Joyce, Virginia Woolf, and T.S. Eliot. It explores how these authors challenged traditional narrative forms and experimented with new literary techniques to reflect the complexities of modern life. The study analyzes the use of stream-of-consciousness, fragmented narrative, and symbolic language in their key works, such as Joyce’s “Ulysses”, Woolf’s “Mrs. Dalloway”, and Eliot’s “The Waste Land”. By investigating these literary innovations, the thesis aims to provide a comprehensive understanding of Modernist literature and its impact on subsequent literary movements.